Handbook of experimental finance - Füllbrunn, Sascha; Haruvy, Ernan (Edward Elgar Publishing, 2022)
"Offering an in-depth overview of the field's past, present, and future, this Handbook provides a comprehensive analysis of the current topics, methodologies, findings, and breakthroughs in research conducted with the help of experimental finance methodology. Suggesting innovative ways of navigating and structuring financial markets, it also showcases the diversity and promise of using experiments in finance. With contributions from leading experts, the Handbook begins with a series of investigations into human behavior in financial decision-making, asking methodological questions regarding subject pool choice, cognitive finance, physical and physiological measurement, and research directions. Stressing the dual nature of experimental finance, chapters then relate to market experiments by exploring applied topics, including bank runs, financial accounting and nudging. Finally, it examines experimental tools and methodologies, critical perspectives, roadmaps for implementation, and empirical testing of finance theories. With examples of experiments that test the fundamental theoretical constructs in finance, this Handbook will prove a vital resource to students and scholars of finance, financial economics, and experimental methodology. It will also prove useful to practitioners and policymakers looking to innovate and experiment with their approaches to financial decision-making"--
Includes bibliographical references and index
Keywords: Handbuch; Aufsatzsammlung; Experiment; Finanzierung